2010
DOI: 10.1089/acm.2009.0372
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Meditation for Refractory Pain and Symptoms

Abstract: Over 50% of patients followed in chronic disease clinics complain of moderate to severe pain. Patients with persistent pain or stress are more likely to be interested in intensive meditation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Participants in this study were asked whether they would be interested in trying meditation; 74% reported interest in learning mind‐body practices during maintenance hemodialysis . Similarly, in a US chronic kidney disease and transplant pain clinic, 39% of respondents reported interest in attending an intensive 10‐day meditation retreat …”
Section: Prevalencementioning
confidence: 99%
“…Participants in this study were asked whether they would be interested in trying meditation; 74% reported interest in learning mind‐body practices during maintenance hemodialysis . Similarly, in a US chronic kidney disease and transplant pain clinic, 39% of respondents reported interest in attending an intensive 10‐day meditation retreat …”
Section: Prevalencementioning
confidence: 99%
“…Many people use meditation to treat stress and stress-related conditions, as well as to promote general health. 1,2 To counsel people appropriately, clinicians need to know more about meditation programs and how they can affect health outcomes. Meditation training programs vary in several ways, including the type of mental activity promoted, amount of training, the use and qualifications of an instructor, and emphasis on religion or spirituality.…”
Section: Introductionmentioning
confidence: 99%
“…The ages of the samples in all studies were between 60 and 90 years old. Eleven articles were reports of studies of pain management among American older adults (Asghari & Nicholas, 2006;Barry et al, 2004;Carson et al, 2005;Cornally & McCarthy, 2011;Decker et al, 2009;Dunn & Horgas, 2004;Goyal et al, 2010;Green et al, 2009;Kemp et al, 2005;Morone et al, 2008;Sawyer et al, 2006). Six articles were reports of studies of pain management among Chinese older adults (Chiou et al, 2009;Gong et al, 2013;Tsai et al, 2010;Tse & Ho, 2013;Tse, Pun, & Benzie, 2005;.…”
Section: Participantsmentioning
confidence: 99%